Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
y + 3= 3(x - 6) ← point-slope form
y = 3x - 21 ← slope-intercept form
3x - y = 21 ← standard form
Step-by-step explanation:
The point-slope form of the equation of line it's y - y₁ = m(x - x₁), where m is the slope and (x₁, y₁) is the point the line passing through.
y=m₁x+b₁ ║ y=m₂x+b₂ ⇔ m₁ = m₂
{Two lines are parallel if their slopes are equal}
y = 3x + 1 ⇒ m₁ = 3 ⇒ m₂ = 3
(6, -3) ⇒ x₁ = 6, y₁ = -3
point-slope form:
y - (-3) = 3(x - 6)
y + 3 = 3(x - 6)
y + 3 = 3x - 18 {subtact 3 from both sides}
y = 3x - 21 ← slope-intercept form
-3x + y = -21 {multiply both sides by (-1)}
3x - y = 21 ← standard form
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.